A matemática como caminho da inclusão escolar - Silva, Carlos Alberto Barbosa (2013)
Social exclusion reaches all segments of society and does not fail to be present in the school environment. This being one of the first social doors open to the individual, nor is always ready to welcome you with their differences. The process of inclusion must be present in all schools is not the privilege of the few on behalf of a majority that is harmed without even knowing what is happening around you. Children with special needs, among them those with Down syndrome, are liable to include numerical, and in this sense the school is a major ally of the family in search of an effective inclusion, what needs to happen to all their agents are focused create opportunities in an inclusive school. Thus, the inclusion of numerical students with special needs, will be established from the encouragement of those involved, parents and school, towards the stimulation of the child, and use of recreational resources appropriate for mediation of the contents to be worked, where through the relationships established will develop the potential of the same logical-mathematical. The teacher is the main feature of a school to promote inclusion as solidarity, to Diakonia.